Technology, Science and Culture A Global Vision - Picazo-Vela, Sergio; Ricardo Hernández, Luis (IntechOpen, 2019)
The aim of the Workshop: Technology, Science, and Culture - A Global Vision is to create a discussion forum on research related to the fields of Water Science, Food Science, Intelligent Systems, Molecular Biomedicine, and Creation and Theories of Culture. The workshop is intended to discuss research on current problems, relevant methodologies, and future research streams and to create an environment for the exchange of ideas and collaboration among participants.